2017
DOI: 10.1093/bja/aex340
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying for liquids of different compositions in children

Abstract: clinicaltrials.gov NCT02938065 clinicaltrials.gov/ct2/show/NCT02938065.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…These two drinks belong to clear fluid but differ in total amount of calories, osmolality, and compositional electrolyte. Previous studies have reported that gastric emptying of clear fluids was mainly dependent on the total amount of calories rather than the volume and type of fluid 24,25 . For example, a slower gastric emptying rate was observed for 500 mL of beverages than that for same volume of other fluids containing higher calories 26 .…”
Section: Discussionmentioning
confidence: 95%
“…These two drinks belong to clear fluid but differ in total amount of calories, osmolality, and compositional electrolyte. Previous studies have reported that gastric emptying of clear fluids was mainly dependent on the total amount of calories rather than the volume and type of fluid 24,25 . For example, a slower gastric emptying rate was observed for 500 mL of beverages than that for same volume of other fluids containing higher calories 26 .…”
Section: Discussionmentioning
confidence: 95%
“…Fourth, because studies have shown little difference in gastric emptying across various types of liquids, we did not analyze the type of liquid administered to our patients before the non per os period. 34 Fifth, although we identified and excluded vital sign artifacts, artifacts could have remained that impacted our findings. 35 Sixth, we were unable to assess clinicians' awareness of fluid fasting time at the time of anesthesia induction and thus did not include it in our analysis as a potential confounder.…”
Section: Perioperative Medicinementioning
confidence: 99%
“…A light breakfast of solids 4 hours prior to surgery has been advocated by some centres and has been reported to empty from the stomach within 4 hours in most children . Schmitz et al used MRI to examine residual GCV four and 6 hours after a light breakfast and found no difference in GCV.…”
Section: Discussionmentioning
confidence: 99%
“…The emptying rate of solids and nonhuman milk depends both on the caloric density and the amount of food ingested . Departments that consider introducing a light breakfast prior to surgery should arguably include a clear description of what kind of food is allowed, as well as both a time limit and a caloric limit .…”
Section: Discussionmentioning
confidence: 99%